2006
DOI: 10.1111/j.1440-1797.2006.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum oxidized low‐density lipoprotein is inversely correlated to telomerase activity in peripheral blood mononuclear cells of haemodialysis patients

Abstract: Ox-LDL serum level is inversely correlated to telomerase activity in PBMC of HD patients. Our study proposes a new consequence of increased oxidative stress in HD patients: the premature cellular senescence potentially related to atherosclerosis through LDL oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…Here we demonstrated that both telomerase activity and expression are affected in patients with a decline in renal function, a fact that might be associated with the increased inflammation markers. These conclusions concur with the results of two previous studies conducted in our laboratory [34,35]. In addition one cannot overlook the negative statistical relationship between the rise in IL-6 serum concentration and the decrease in telomerase activity.…”
Section: Discussionsupporting
confidence: 93%
“…Here we demonstrated that both telomerase activity and expression are affected in patients with a decline in renal function, a fact that might be associated with the increased inflammation markers. These conclusions concur with the results of two previous studies conducted in our laboratory [34,35]. In addition one cannot overlook the negative statistical relationship between the rise in IL-6 serum concentration and the decrease in telomerase activity.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies on haemodialysis and diabetic patients [18], [19] and patients with rheumatoid arthritis [20] have found lower PBMC telomerase activity suggesting that in a cell type like PBMC, which is directly implicated in the inflammatory process, it is generally expected a pre-mature senescence for a higher inflammatory activity [21]. On the other hand, PBMC telomerase levels measured in our study are comparable with those recently reported for overweight African Americans [22].…”
Section: Discussionsupporting
confidence: 83%
“…The higher concentration of oxLDL found in serum of HD patients in our study could reflect the increased LDL oxidation, and is in keeping with previous reports [26,27,28]. It has been shown that in chronic renal failure, increased LDL oxidation could be attributed to a decrease in the activity of certain enzymes with a HDL-related antioxidant effect, such as paraoxonase and lecithin-cholesterol acyltransferase (LCAT) [6,15,29,30,31].…”
Section: Discussionsupporting
confidence: 82%